Medical Students and the Hope of Health Justice - Tirtakusuma, Shamma Jezzaniah; Tirtakusuma, Andreas Eno (Journal of Law, Politic and Humanities, 2025)
This research uses a qualitative library research approach to examine the disparity in healthcare access and its impact on health equity in Indonesia. The study focuses on the concepts of health access and health equity, particularly in addressing the challenges faced by marginalized communities in remote and rural areas, such as Papua, compared to more developed urban regions like Jakarta. By analyzing secondary data, including legal documents like the 1945 Constitution of Indonesia and Law No. 17 of 2023 concerning Health, along with scholarly articles and NGO reports, the research aims to highlight systemic barriers such as geographical, financial, and service quality limitations. The study emphasizes the importance of equitable access to healthcare as a critical component of achieving health equity. The findings suggest that while significant progress has been made, much remains to be done to address these disparities and ensure that all citizens, regardless of their social or geographic status, have equal opportunities to achieve optimal health. This research also explores the role of healthcare professionals, community service programs, and innovations in health technology as solutions to these challenges.